Diaspora philanthropy: the making of a new development aid?. (1st September 2016) - Espinosa, Shirlita Africa
Abstract : The article is a critical engagement that answers the 'what', 'for whom' and 'how' of diaspora philanthropy. Diaspora philanthropy, although very much an important part of migrant economic and cultural life, is hardly theorised. It does not attract as much attention as remittances, although both are poised to make significant contribution to development. Given the decreasing amount of official development aid to the developing world, migrant philanthropy and remittances are being groomed as the new development aid, and migrants, the enabler of development. Under the banner of migration–development nexus, diaspora philanthropy promotes the active participation in the development of sending countries by diaspora communities. In this article, I argue that flexibility is diaspora philanthropy's characteristic that allows it to serve the purposes of migration governance bodies and be absorbed by their discourse. Moreover, I also examined how diaspora philanthropy, or the migration–development nexus more broadly, is a response to crisis globally felt and needed a synergised solution that migrants and the wealth they created can provide. While the potential of diaspora philanthropy is recognised by economic managers, its principles may not be as easy to execute. I then use the experiences of Philippines' LINKAPIL program to outline the challenges that pose difficulties in the implementation of diaspora philanthropy. In sum, the article questions whether the promise ascribed to diaspora philanthropy has a strong basis to be realised in the name of development.